The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1002/1878-0261.12157
|View full text |Cite
|
Sign up to set email alerts
|

Dual inhibition of DNMTs and EZH2 can overcome both intrinsic and acquired resistance of myeloma cells to IMiDs in a cereblon‐independent manner

Abstract: Thalidomide and its derivatives, lenalidomide and pomalidomide (also known as IMiDs), have significantly changed the treatment landscape of multiple myeloma, and the recent discovery of cereblon (CRBN) as their direct biological target has led to a deeper understanding of their complex mechanism of action. In an effort to comprehend the precise mechanisms behind the development of IMiD resistance and examine whether it is potentially reversible, we established lenalidomide‐resistant (‐LR) and pomalidomide‐resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 52 publications
1
55
1
Order By: Relevance
“…Within the 22 paired samples examined, although a fraction of patients showed increased CRBN expression, there was a significant reduction in CRBN expression after Ld therapy. A reduction of CRBN could facilitate the non‐CRBN‐dependent process of proliferation/survival in MM cells and contribute to the poor sensitivity to IMiDs.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Within the 22 paired samples examined, although a fraction of patients showed increased CRBN expression, there was a significant reduction in CRBN expression after Ld therapy. A reduction of CRBN could facilitate the non‐CRBN‐dependent process of proliferation/survival in MM cells and contribute to the poor sensitivity to IMiDs.…”
Section: Discussioncontrasting
confidence: 99%
“…As there was significantly reduced CRBN expression in the post‐Ld samples, we explored the methylation status of the CRBN promoter; there was no hypermethylation in the promotor in the clinical samples. This is consistent with the observations by Dimopoulos et al, who showed no involvement of promoter methylation in the regulation of CRBN expression in Len‐resistant MM cell lines. However, the mechanism by which CRBN expression is downregulated remains to be understood.…”
Section: Discussionmentioning
confidence: 99%
“…To test whether epigenetic alterations are involved in the interconversion between SP and NSP cells, we performed Acce SssI ble assay to measure DNA methylation and chromatin accessibility in these two subpopulations. The Acce SssI ble assay was developed in our group and has been used successfully to identify potential epigenetic driver genes in renal cell carcinoma as well as epigenetic changes after epigenetic therapy . Acce SssI ble assay couples the analysis of chromatin accessibility and endogenous DNA methylation using the Infinium MethylationEPIC BeadChip array platform, requires very little input material, is cost‐effective, and uses simple and straightforward computational techniques for analysis …”
Section: Resultsmentioning
confidence: 99%
“…The AcceSssIble assay was developed in our group 24 and has been used successfully to identify potential epigenetic driver genes in renal cell carcinoma 22 as well as epigenetic changes after epigenetic therapy. 23,24,29 AcceSssIble assay couples the analysis of chromatin accessibility and endogenous DNA methylation using the Infinium MethylationEPIC BeadChip array platform, requires very little input material, is cost-effective, and uses simple and straightforward computational techniques for analysis. 22,24 Differences in global DNA methylation and chromatin accessibility levels between SP and NSP cells of J82 were calculated and plotted, and six groups (a-f ) of loci with differential methylation and/or accessibility were designated ( Figs.…”
Section: Differential Chromatin Accessibility and Dna Methylation Betmentioning
confidence: 99%
“…However, MM remains largely incurable due to inevitable relapse and development of chemoresistance (Teoh et al ., 2014). Development of novel therapeutic approaches and targeting of abnormal cancer metabolism in molecular and cellular heterogeneity of MM may provide us with new strategies for overcoming this disease (Dalva‐Aydemir et al ., 2015; Dimopoulos et al ., 2018; Naymagon and Abdul‐Hay, 2016). …”
Section: Introductionmentioning
confidence: 99%